From Verbal to Audiovisual Medium: The Case of the Cinematic Adaptation of R. L. Stevenson’s Novel “The Wrong Box”. Part I - Krūminienė, Jadvyga; Višinskaitė, Indrė (Respectus Philologicus, 2018)
The paper attempts at the analysis of the narrational shifts between verbal and audiovisual mediums on the basis of R. L. Stevenson’s novel The Wrong Box (1989) and its cinematic adaptation under the same title by Bryan Forbes (1966). The authors approach adaptation as a complex phenomenon that experiences the creative tension between preserving fidelity to the source literary text and striving for filmic originality. Similarly to novels, movies represent an act and art of narration but they use different narrative strategies. In film narratives, deep focus, the length and scale of the shots, editing, montage, lighting, sound design, music, human voice etc. accompany the verbal medium. Modelled after literature, movies demonstrate the specific construal narrative components that are combined into coherent cinematic sequences. When transfering R. L. Stevenson’s novel from fictional medium into cinematic medium, Forbes organises the relations of the narrative elements on an intertextual level thus fostering new expressive means. Such practice allows to project the cinematic narrator as a complex construct also given the possibility of being perceived as a speaking persona through an inventive use of intertitles. In fact, the adaptor is caught up in the farcical narrational game, provoking the viewer to actively participate in it.